2020
DOI: 10.1042/bsr20193738
|View full text |Cite
|
Sign up to set email alerts
|

Ma xing shi gan decoction eliminates PM2.5-induced lung injury by reducing pulmonary cell apoptosis through Akt/mTOR/p70S6K pathway in rats

Abstract: Abstract The present study was designed to investigate the anti-apoptosis effect of Ma xing shi gan decoction (MXD) on PM2.5-induced lung injury via protein kinase B (Akt)/mTOR/p70S6K pathway. A UPLC-MS/MS system was introduced for component analysis of MXD. Rats were instilled with PM2.5 solution suspension intratracheally to induce acute lung injury. The rats were then orally administered with MXD (16, 8, and 4 g/kg) once a day for 7 consecutive days. The thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…AKT/mTOR signaling, a classical autophagy-related pathway, has been implicated in the mechanism investigation about ALI in previous studies [ 30 , 31 ]. To further identify the potential mechanisms of Octreotide mediate cell autophagy in ALI model, the protein levels of related factors in AKT/mTOR signaling were determined using Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…AKT/mTOR signaling, a classical autophagy-related pathway, has been implicated in the mechanism investigation about ALI in previous studies [ 30 , 31 ]. To further identify the potential mechanisms of Octreotide mediate cell autophagy in ALI model, the protein levels of related factors in AKT/mTOR signaling were determined using Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Originating from the "Shang Han Lun," MaXingShiGan Decoction (MSXG) is a traditional Chinese formula composed mainly of Ephedra sinica Stapf [Ephedraceae; HERBA EPHEDRAE] (MaHaung, MH), Prunus armeniaca L. [Rosaceae; Semen Armeniacae Amarum] (KuXingRen, KXR), Gypsum Fibrosum [Mineral; Gypsum] (ShiGao, SG), and Glycyrrhiza glabra L. [Fabaceae; RADIX GLYCYRRHIZAE] (GanCao, GC). It itself and the derivative formulas such as Lianhua Qingwen Capsules, Han Shi Yi Formula, QingFeiPaiDu Decoction, are commonly employed to treat upper respiratory infections, acute bronchitis, pneumonia, bronchial asthma, and played a pivotal role in the management of the COVID-19 pandemic in China (Zhu and Liu, 2004;Liao et al, 2017;Wang et al, 2020a;Wang et al, 2020b;Tian et al, 2020;Xiao et al, 2020). Additionally, a prior randomized, double-blind, placebo-controlled, multicenter clinical study that we conducted demonstrated the efficacy of MSXG in effectively treating community-acquired childhood pneumonia and significantly improving fever and other clinical symptoms (Zheng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%